Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Classification internationale: modèle de développement humain - processus de production du handicap (MDH-PPH) - Cloutier, Chantal; Poulin, Marie-Michelle; Sauvé, Méric; Fougeyrollas, Patrick; Cloutier, René; Bergeron, Hélène; Réseau international sur le processus de production du handicap (RIPPH, Réseau international sur le Processus de production du handicap, 2018)
La Classification internationale : Modèle de Développement humain – Processus de production du handicap (2018) comprend le schéma conceptuel du MDH-PPH, les définitions des domaines conceptuels « habitudes de vie », « facteurs environnementaux » et « facteurs personnels » et leurs différentes nomenclatures. Ce document de référence se révèle utile pour classer l’information disponible de manière cohérente en respectant le principe d’exclusion mutuelle des concepts, central à l’approche du MDH-PPH.
Section: 246 pages : tableaux, graphiques en couleur ; 28 cm
Keywords: EDI; approches et analyses; capacitisme; cours; discipline; médecine; premier cycle; santé; sciences; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Les droits sexuels des personnes handicapées: réflexion sur le développement du droit international - Mona Paré (Genre, Sexualité et Société, 2018)
Interest in the sexuality of persons with disabilities is growing and research improves our understanding of issues in this regard. This leads us to a reflection on the definition of sexual rights in international law, and the way in which sexual rights of persons with disabilities are understood. Examining existing norms leads to the conclusion that despite developments in this area, sexual rights remain largely limited to the field of health, and this has not changed with the adoption of the Convention on the Rights of Persons with Disabilities (CRPD). The limited claims related to these rights during the negotiations of the CRPD is surprising given the significant participation of persons with disabilities. Yet, despite the lack of clarification in relation to the sexual rights of persons with disabilities in the convention, the practice of interpretation of law remains a way to develop international law in this field, particularly through the evolving concept of non-discrimination.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; approches et analyses; capacitisme; cours; discipline; droit; droit des personnes en situation de handicap; droit international; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; santé; science politique et droit; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice–one of the most important and ground-breaking subjects to have emerged in philosophy in recent years–refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Le chap 10 de Patricia Hill Collins, “Intersectionality and Epistemic Injustice” a été donné en lcture au cours FEM9000. Le chap 14 de Kim Hall, “Queer Epistemology and Epistemic Injustice” a été donné en lecture au cours FEM9000. Le chap 15 de Rachel McKinnon, “Allies behaving badly: Gaslighting as epistemic injustice” a été donné en lecture au cours FEM9000. Le chap 16 de Shelley Tremain, “Knowing Disability Differently” a été donné au cours FEM9000. Le chap 33 de Anastasia Scrutton, “Epistemic Injustice and Mental Illness” a été donné en lecture au cours FEM9000. Le chap 34 de Rebecca Tsosie, “Indigenous peoples, anthropology, and the legacy of epistemic injustice” a été donné au cours FEM9000.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

(Re)penser l’accès aux espaces intimes en contexte de handicap intellectuel: une question de droit et de participation sociale - Pariseau-Legault, Pierre; Holmes, Dave (Revue générale de droit, 2017)
En contexte de handicap, la question de l’accès est constituée généralement de l’éventail des aménagements individuels et collectifs nécessaires afin de faciliter l’occupation d’espaces publics. A contrario, peu de choses sont dites à propos des aménagements possibles et potentiels requis afin de sécuriser l’espace privé des personnes identifiées comme ayant un handicap intellectuel. Ce sont pourtant ces lieux intimes, au sein desquels se développent et se déploient l’identité et l’expression affectives, qui sont susceptibles de contribuer à une reconnaissance plus soutenue de l’identité affective et de la citoyenneté sexuelle de ces personnes. Inspirée par les théories d’Erving Goffman et de Michel Foucault, une analyse phénoménologique interprétative (API) fut réalisée auprès des personnes ayant un handicap intellectuel et de leurs proches aidants afin d’explorer cette situation. Nos constats préliminaires suggèrent l’existence d’un processus de négociation complexe des acteurs, des lieux et des moments nécessaires afin de favoriser le développement de la vie affective et sexuelle. De ce fait, trois modes d’existence semblent cohabiter au sein d’une matrice complexe : la dépossession, l’habitation et l’occupation des espaces de socialisation et d’expression affective. Il est proposé d’aborder cette problématique en tant que dynamique géopolitique intégrant les processus d’exclusion des pratiques sexuelles des espaces privés, leur projection dans des espaces publics et, finalement, la juxtaposition de ces deux sphères, publique et privée dans des espaces mixtes. Nous discuterons enfin des implications de cette réflexion sur la « question de l’accès » et sur les politiques publiques visant à diminuer la discrimination systémique ciblant les personnes identifiées comme ayant un handicap intellectuel.
Keywords: approches et analyses; capacitisme; care; corps; cours; discipline; droit; histoire et politique; inégalités; justice sociale; premier cycle; ressource en ligne; santé; science politique et droit; science politique et droit de la santé; sciences; sciences de la santé; sciences politiques; sex1920; sexualité; systèmes d'oppressions; thématiques

Robert McRuer on Crip Theory - CP-assistenten (2016)
Interview of Robert McRuer on crip theory.
Keywords: EDI; approches et analyses; arts; capacitisme; cours; discipline; histoire et politique; premier cycle; ressource en ligne; santé; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Dis/ability studies: theorising disablism and ableism - Goodley, Dan (Routledge, 2014)
In this ground-breaking new work, Dan Goodley makes the case for a novel, distinct, intellectual, and political project – dis/ability studies – an orientation that might encourage us to think again about the phenomena of disability and ability. Drawing on a range of interdisciplinary areas, including sociology, psychology, education, policy and cultural studies, this much needed text takes the most topical and important issues in critical disability theory, and pushes them into new theoretical territory. Goodley argues that we are entering a time of dis/ability studies, when both categories of disability and ability require expanding upon as a response to the global politics of neoliberal capitalism. Divided into two parts, the first section traces the dual processes of ableism and disablism, suggesting that one cannot exist without the other, and makes the case for a research-driven and intersectional analysis of dis/ability. The second section applies this new analytical framework to a range of critical topics, including: The biopolitics of dis/ability and debility Inclusive education Psychopathology Markets, communities and civil society. Dis/ability Studies provides much needed depth, texture and analysis in this emerging discipline. This accessible text will appeal to students and researchers of disability across a range of disciplines, as well as disability activists, policymakers, and practitioners working directly with disabled people.
Section: xvii, 204 pages ; 25 cm
Keywords: EDI; approches et analyses; capacitisme; care; corps; cours; discipline; interdisciplinarité; lit4700; premier cycle; psychologie; pédagogie; santé; sciences de l'éducation; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Disability and difference in global contexts: enabling a transformative body politic - Erevelles, Nirmala (Palgrave Macmillan, 2011)
« This book explores the possibilities and limitations re-theorizing disability using historical materialism in the interdisciplinary contexts of social theory, cultural studies, social and education policy, feminist ethics, and theories of citizenship. »– Résumé de l'éditeur.
Keywords: EDI; approches et analyses; capacitisme; corps; cours; discipline; pol4212; premier cycle; santé; systèmes d'oppressions; thématiques; études critiques du handicap